COOPERATIVE BLOCK-PARALLEL ALGORITHMS FOR TASK EXECUTION ON MULTI-CORE SYSTEM - A. A. Prihozhy; O. N. Karasik (Системный анализ и прикладная информатика)
The problem of balancing the computational load among the cores of a multicore system and increasing the efficiency of interaction among threads in a multithread application is considered. The cooperative blockparallel algorithms of solving complex tasks that can be decomposed into subtasks, which decrease the number of control transfers among threads, reduce the critical path length in a parallel implementation and increase the cores load are proposed.